Peningkatan Pengetahuan Orang Tua Mengenai Gizi Kurang pada Balita dengan Metode Intervensi Edukasi - Kristanti, Melly; Harjono, Yanti; Arvant, Anisya Zakiyyahaya; Dirgantara, Dandi Tri; Suci, Shabrina Amalia; Nurmaulida, Fadhila (Universitas Baiturrahim, 2024)
The nutritional status of children is an important thing that every parent must know, because disturbances that occur due to unbalanced nutrition will cause irreversible damage. In 2018, the prevalence of malnutrition in the world was 7.3% or ± 49.5 million children.The problem experienced by this community is that there are still high cases of malnutrition in toddlers in the working area of the Cipayung Health Center, so there is a need for education and intervention for the community regarding the prevention and prevention of malnutrition. The results of this activity were an increase in knowledge of malnutrition p-value 0.021 and the attitude of obedience of parents in providing supplementary food to their undernourished children. This is very important to do in various working areas of the puskesmas and in the community itself, because prevention from an early age can reduce the high incidence of malnutrition which has an impact on the death rate in Indonesia